(untitled) (Revista Contexto & Saúde, 2025)
Objective: To summarize the evidence on pharmacological treatment and its relationship with self-care in individuals with rheumatoid arthritis. Method: This scoping review was conducted in the first half of 2023. Articles published since 1985 were included, covering indexed journals, gray literature, and reference lists, with no language restrictions. Study selection was performed using Rayyan software, and data were extracted using a standardized questionnaire in Excel. The protocol was registered on the Open Science Framework (doi.org/10.17605/OSF.IO/H3SZK). Results: A total of 31 studies published between 1999 and 2022 were retrieved, mostly cross-sectional and published in English. The most frequently reported factors related to pharmacological treatment and changes in self-care included medication side effects, number of medications, indefinite treatment duration, self-medication, knowledge of treatment, positive treatment effects, as well as fear and negative beliefs. Conclusion: The relationship between self-care and pharmacological treatment in individuals with rheumatoid arthritis involves multiple variables. An individualized approach may facilitate the understanding of specific factors for each person and support the management of improved self-care.